Pertimbangan Putusan Hakim Pra Peradilan Mengenai Sah Tidaknya Penetapan Tersangka: Considerations of Pretrial Judges’ Decisions Regarding The Validity of Suspect Determinations - Khaerul Umam; Alwan Hadiyanto; Wijayono Hadi Sukrisno (Universitas Semarang, 2025)
This study examines the scope of judicial authority in adjudicating pretrial motions, the underlying judicial reasoning concerning the validity of suspect determinations, and the ensuing legal implications, with a specific focus on Decision No. 1/Pid.Pra/2024/PN Unr. The urgency of this inquiry emerges from the imperative to safeguard human rights and prevent the misuse of state power in law enforcement, particularly after Constitutional Court Decision No. 21/PUU-XII/2014 broadened the jurisdiction of pretrial mechanisms. Employing a normative juridical method combined with statutory and case approaches, the analysis adopts a qualitative lens to assess judicial interpretations and practices. The findings reveal that the pretrial judge upheld the legality of the suspect determination on the basis of adequate preliminary evidence and the circumstance of being caught in flagrante delicto. The study underscores that judicial reasoning in such cases remains predominantly formalistic, often neglecting substantive justice and thereby generating inconsistencies in legal standards. Within this context, pretrial proceedings are positioned as a vital judicial safeguard against investigative arbitrariness, yet they continue to face the complex task of reconciling legal certainty with equitable justice. By engaging Hans Kelsen’s theory of legal certainty and Gustav Radbruch’s concept of justice, this research offers a critical reflection on the philosophical underpinnings of pretrial review. It calls for the establishment of standardized judicial guidelines, clearer jurisprudential direction from the Supreme Court, and enhanced integrity among law enforcement agencies to ensure that pretrial institutions genuinely function as instruments of justice and human rights protection. Penelitian ini mengkaji kewenangan hakim dalam memeriksa permohonan praperadilan, pertimbangan yuridis terhadap keabsahan penetapan tersangka, serta akibat hukum dari putusan tersebut, dengan studi kasus pada Putusan Nomor 1/Pid.Pra/2024/PN Unr. Urgensi penelitian ini berangkat dari pentingnya perlindungan hak asasi manusia dan pencegahan penyalahgunaan kewenangan aparat penegak hukum, terutama pasca Putusan Mahkamah Konstitusi Nomor 21/PUU-XII/2014 yang memperluas ruang lingkup kewenangan praperadilan. Metode yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan dan kasus, serta analisis kualitatif terhadap pertimbangan hukum hakim. Hasil penelitian menunjukkan bahwa hakim praperadilan menyatakan penetapan tersangka sah dengan alasan adanya bukti permulaan yang cukup serta kondisi tertangkap tangan (in flagrante delicto). Meskipun demikian, pertimbangan hakim masih cenderung bersifat formalistik dan belum sepenuhnya mencerminkan keadilan substantif, sehingga menimbulkan ketidakkonsistenan dalam standar objektif penilaian. Dalam konteks ini, praperadilan memiliki posisi strategis sebagai mekanisme kontrol yudisial terhadap tindakan penyidikan, namun tetap menghadapi tantangan dalam menyeimbangkan kepastian hukum dengan keadilan yang substansial. Dengan merujuk pada teori kepastian hukum Hans Kelsen dan teori keadilan Gustav Radbruch, penelitian ini memberikan refleksi kritis atas fondasi filosofis praperadilan di Indonesia. Ditekankan perlunya pedoman peradilan yang terstandardisasi, penguatan arah yurisprudensi oleh Mahkamah Agung, serta peningkatan integritas aparat penegak hukum agar lembaga praperadilan benar-benar berfungsi sebagai instrumen keadilan dan perlindungan hak asasi manusia.